2023
DOI: 10.1093/plphys/kiad447
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentation of photosynthesis gene expression in C4 maize depends on time of day

Abstract: Compared with the ancestral C3 state, C4 photosynthesis occurs at higher rates with improved water and nitrogen use efficiencies. In both C3 and C4 plants, rates of photosynthesis increase with light intensity and are maximal around midday. We determined that in the absence of light or temperature fluctuations, photosynthesis in maize (Zea mays) peaks in the middle of the subjective photoperiod. To investigate the molecular processes associated with these temporal changes, we performed RNA-sequencing of maize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 78 publications
1
4
0
Order By: Relevance
“…We investigated the variable enzymes that give each C 4 subtype its unique properties by focusing on two species (S. bicolor and Z. mays) from the NADP-ME subtype (Figure 3A). As expected, chromatin accessibility bias was observed for enzymes previously reported as having cell-type-specific expression patterns, similarly to the core C 4 enzyme set (23,29). Reassuringly, one of the most biased enzymes identified was NADP-ME, the key enzyme of the redox step in NADP-ME subtypes.…”
Section: Key C 4 Subtype Enzymes Show Potential Convergent Evolution ...supporting
confidence: 74%
“…We investigated the variable enzymes that give each C 4 subtype its unique properties by focusing on two species (S. bicolor and Z. mays) from the NADP-ME subtype (Figure 3A). As expected, chromatin accessibility bias was observed for enzymes previously reported as having cell-type-specific expression patterns, similarly to the core C 4 enzyme set (23,29). Reassuringly, one of the most biased enzymes identified was NADP-ME, the key enzyme of the redox step in NADP-ME subtypes.…”
Section: Key C 4 Subtype Enzymes Show Potential Convergent Evolution ...supporting
confidence: 74%
“…Previous studies have identified a small number of cis - and trans -regulatory mechanisms that control the specific expression of C 4 genes in mesophyll and bundle sheath cells (Marshall et al, 1997; Gowik et al, 2004; Akyildiz et l., 2007; Brown et al, 2011; Williams et al, 2016; Reyna-Llorens et al, 2018; Borba et al, 2023). The expression patterns driven by these cis -regulatory sequences in C 3 and C 4 species suggest that rewiring of ancestral gene regulatory mechanisms underlies the evolution of cell type specific gene expression required for C 4 photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, DOF transcription factor binding sites were enriched in chromatin regions that were specifically accessible in bundle sheath cells of both rice and sorghum. Supporting this, transient expression assays in C4 maize have shown that DOF transcription factors are able to activate the expression of NADP-ME and PEPCK, two genes that are specifically expressed in the bundle sheath (Borba et al, 2023). Thus, in contrast to the low level of conservation of transcriptional identities detected for the bundle sheath between C3 rice and C4 sorghum, it appears that the cisregulatory landscape regulating cell-type specific expression is conserved between the two species.…”
Section: C4 Gene Expression Exapts Gene Regulatory Network Associated...mentioning
confidence: 96%
See 2 more Smart Citations